The Effect of Cross-Border Mergers and Acquisitions on Cost Efficiency of Commercial Banks in China: A Stochastic Frontier Analysis - JI, XU (2015)
With the liberalization of economy and globalization, business communications among nations has become more frequently. The same is true as the cooperation and competition between financial institutions from different countries. Under such condition, there is a driving trend of large-scale mergers and acquisitions (M&A) activities worldwide. China, as one of the outstanding representatives of emerging economies, has achieved high-speed in economic growth. Many commercial banks of China have set about the cross-border mergers and acquisitions not only to promote the international influence but also to increase their profitability and efficiency. This paper uses the Stochastic Frontier Analysis (SFA) model to examine the relationships between mergers and acquisitions and cost efficiency in Chinese bank industry. According to the announcement time of mergers and acquisitions, the two groups that pre and post mergers and acquisitions groups are built. The changed value of cost efficiency in the two groups may reflect the effect of mergers and acquisitions. The main finding of this paper suggests that the mergers and acquisitions have significant positive effect on cost efficiency of Chinese banks. Key words: Cross-border M&A, Chinese bank industry, SFA